1998
DOI: 10.1111/j.1151-2916.1998.tb02720.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Synthesis of Yttrium Iron Garnet Powder

Abstract: A 28 GHz microwave heating method was used to react an Fe2O3+ Y2O3 powder mixture to form yttrium iron garnet (YIG, Y3Fe5O12) powder. The minimum temperature to form YIG was lower than the conventional (external) heating method. YIG began to form after only 70 s of irradiation, which means that the solid‐state reaction proceeded very rapidly. The amounts of byproducts were controlled by the starting composition and by the Y2O3 particle size. The resultant YIG particle size also was controlled by the Y2O3 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The time for the synthesis of yttrium iron garnet significantly reduces. This is attributed to both the rapid heating of the starting component and the nonthermal effect of the microwave field on the interdiffusion of the components [6]. The rapid formation of YVO 4 : Eu +3 under MWH is also attributed to the intensive heating of the mixture due to the strong microwave absorptivity of vanadium oxide present in the starting powder mixture [7].…”
mentioning
confidence: 94%
“…The time for the synthesis of yttrium iron garnet significantly reduces. This is attributed to both the rapid heating of the starting component and the nonthermal effect of the microwave field on the interdiffusion of the components [6]. The rapid formation of YVO 4 : Eu +3 under MWH is also attributed to the intensive heating of the mixture due to the strong microwave absorptivity of vanadium oxide present in the starting powder mixture [7].…”
mentioning
confidence: 94%
“…On the other hand, ␣-Fe 2 O 3 showed a moderate temperature increase, with a saturation temperature of 260°C at 2 kW. It is quite curious that ␣-Fe 2 O 3 showed moderate coupling with microwaves in this study, because the temperature of ␣-Fe 2 O 3 rapidly increased to 680°C at 1 kW in our previous study 10 are different in each other (but the purity and the particle-size grades are the same), so the difference in surface structure or defect concentration may cause a difference in microwave-material coupling. Additional study is needed to clarify this problem.…”
Section: Methodsmentioning
confidence: 54%
“…[28][29][30][31][32] Recently, Binner et al showed that ZnO grain growth was clearly enhanced by microwaves. 29) They compared microwave/conventional hybrid heating with a pure conventional method for samples that had identical thermal histories.…”
Section: Microstructure Of Tio 2 -Sno 2 Pelletmentioning
confidence: 99%